2021
DOI: 10.3389/fnut.2021.672754
|View full text |Cite
|
Sign up to set email alerts
|

Increased Household Income Improves Nutrient Consumption in Pakistan: A Cross-Sectional Study

Abstract: The provision of high-quality food is a primary factor in ensuring adequate nourishment and preventing malnourishment-related diseases in Pakistan. This study, therefore, aimed to quantify the impact of income on nutrient consumption in Pakistan, with the hypothesis that income has a primary role in reducing malnourishment in the developing world. To do this, we estimated nutrient–income elasticity—defined as the proportion of change in nutrient consumption in response to a change in income—for total calories,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 28 publications
(54 reference statements)
0
12
0
Order By: Relevance
“…The alleviation of time poverty that afflicts mothers ( 31 , 32 ), allowed the mothers to better care for all members of their households, including themselves, a finding that supports previous research ( 33 , 34 ). Mothers also reported new levels of financial independence, a critical pathway for improving maternal and child health and nutrition ( 25 , 35 , 36 ). While facilitating factors such as education about the nutritional value of eggs and ongoing spousal support allowed for continued IYC egg consumption at follow-up, egg availability emerged as an important constraint, limiting the frequency of IYC egg consumption, even among women where motivation remained high.…”
Section: Discussionmentioning
confidence: 99%
“…The alleviation of time poverty that afflicts mothers ( 31 , 32 ), allowed the mothers to better care for all members of their households, including themselves, a finding that supports previous research ( 33 , 34 ). Mothers also reported new levels of financial independence, a critical pathway for improving maternal and child health and nutrition ( 25 , 35 , 36 ). While facilitating factors such as education about the nutritional value of eggs and ongoing spousal support allowed for continued IYC egg consumption at follow-up, egg availability emerged as an important constraint, limiting the frequency of IYC egg consumption, even among women where motivation remained high.…”
Section: Discussionmentioning
confidence: 99%
“…To compute the calorie consumption amount from the reported food quantities, we applied the conversion factors from Food Composition Table for Pakistan ( 31 ), which contains data on nutrient contents for various food items [for details of data extraction, refer to the study by ( 4 )]. For example, the nutrient consumed of a particular type like calorie is as follows:…”
Section: Datamentioning
confidence: 99%
“…where N is the quantity of the particular nutrient consumed, θ i is the average nutrient content of a unit of food i , and Q i is the number of units consumed of food i ( 4 ).…”
Section: Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Van den Broeck et al (2021) confirmed that income growth in rural Tanzania improves nutrition, both in terms of calorie quantity and food quality [ 8 ]. Other studies such as Ogundari et al (2016) and Colen et al (2018) for sub-Saharan Africa and Africa [ 9 , 10 ], Thi et al (2018) for Vietnam [ 11 ], Bhuyan et al (2020) for India [ 12 ], Shabnam et al (2021) for Pakistan [ 13 ], and Ali et al (2018) for Nepal [ 14 ] have also found a positive relationship between income and calorie demand. However, another strand of literature suggests that calorie demand is income-inelastic, which indicates that households are able to smooth calorie consumption even if income changes.…”
Section: Introductionmentioning
confidence: 99%